Peran Sutradara dalam Pembuatan Karya Video Feature “Thrift or Threat: Health Issues in the Thrifting Phenomenon” Dengan Pendekatan Storytelling - Muhammad Arif Rahman; Dian Wardiana Sjuchro; Agus Setiaman (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Thrifting, while a popular affordable fashion alternative, raises concerns about safety and health risks for enthusiasts. The feature video "Thrift or Threat: Health Issues in The Thrifting Phenomenon" aims to raise public awareness, especially among younger generations, regarding the importance of hygiene and health when buying and wearing thrifted clothing. This work also provides accurate information on potential risks and preventive measures, while inspiring other content creators to address relevant social and health issues related to contemporary youth lifestyles. As director, the author gathered information and explored problems through direct interviews at Cimol Gedebage Market. The video's narrative structure employs a storytelling approach based on Freytag's Pyramid, with clear scene divisions: exposition, rising action, climax, falling action, and resolution. Findings indicate the director's crucial role in guiding the entire production process, from research and planning to filming and overseeing editing. This video is expected to enhance public awareness about hygiene and health in thrifting, and serve as an inspiration for content creators exploring pertinent social and health topics.